GAMBARAN KINERJA PEGAWAI DARI SUDUT PANDANG WORK FAMILY CONFLICT MELALUI KEPUASAN KERJA (Studi pada: Pegawai Wanita di Sektor Perbankan Kota Medan) - Sarah Imelda; Ezzah Nahrisah (LPPM STIE EKA PRASETYA, 2019)
This Study aims to describe the performance of female employees in the Medan banking sector in terms of work family conflict and job satisfaction. In order to achieve the objectives of this study, the researchers used the distribution of questionnaires (questionaire) and in-depth interviews (indepth interview) with employees, especially women in the banking sector in the city of Medan. The researcher spreads the list of questions (questionaire) directly to the employees. The population in this study were female employees who worked in the banking sector of the city of Medan. The research sample amounted to 100 people. This research is a quantitative and qualitative descriptive study. The data analysis technique used in this study is multiple linear regression analysis through path analysis. The results showed that (1) Work Family Conflict had a significant positive effect on Employee Performance, (2) Work Family Conflict had a significant positive effect on Job Satisfaction, (3) Job Satisfaction mediated Work Family Conflict on Employee Performance.